2005
DOI: 10.1111/j.1532-5415.2005.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Do‐Not‐Resuscitate and Do‐Not‐Hospitalize Directives of Persons Admitted to Skilled Nursing Facilities Under the Medicare Benefit

Abstract: Ethnic minorities are less likely to have DNR and DNH directives even after controlling for disease status, demographic, facility, and geographic characteristics. Wide variation in the likelihood of having DNR and DNH directives between states suggests a need for better-standardized methods for eliciting the care preferences of residents admitted to SNFs under the Medicare benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 32 publications
5
48
1
Order By: Relevance
“…Caucasian patients, whose emphasis is on autonomy, are more likely to know about and have completed advance directives and DNR orders than African American, Hispanic, and Asian patients. [210][211][212] Factors predicting acceptance of advance directives include education level, prior experience with ventilators, availability of family, severity of illness, and age. 213 Hispanic and African American patients note that there is less need for an advance directive due to expected family roles in medical decision-making.…”
Section: Family-centered and Patient-centered Decision Makingmentioning
confidence: 99%
“…Caucasian patients, whose emphasis is on autonomy, are more likely to know about and have completed advance directives and DNR orders than African American, Hispanic, and Asian patients. [210][211][212] Factors predicting acceptance of advance directives include education level, prior experience with ventilators, availability of family, severity of illness, and age. 213 Hispanic and African American patients note that there is less need for an advance directive due to expected family roles in medical decision-making.…”
Section: Family-centered and Patient-centered Decision Makingmentioning
confidence: 99%
“…Previous studies have shown either a trend towards increased DNR prevalence in women or a lack of association of gender with DNR orders. 8,9,11,12 Gender was not significant in the third simplified model. Gender was significant in the model, which included POA and living will as independent variables, but was involved in an interaction with POA.…”
Section: Resultsmentioning
confidence: 72%
“…Some authors have shown a relationship with race, which was not found in this study, possibly due to the inclusion of confounders in past analyses. 8,9,11,12 In the multivariate analysis, patients of increasing age were significantly more likely to present with a DNR order. Previous studies have consistently demonstrated similar associations with age.…”
Section: Resultsmentioning
confidence: 96%
“…Several prior studies have similarly found lower survival after CPR in black patients compared to white [10,[19][20][21][22], and reasons may include more heart disease [21], less control of heart disease risk factors [21], less access to clinical care [10], receipt of lower quality care [23], a lower prevalence of ventricular fibrillation as the initial cardiac rhythm [10,24], and delayed defibrillation in the hospital [10]. Additionally, black and Hispanic patients may prefer more aggressive life-sustaining treatment than whites and therefore are more likely to receive CPR before death [25], less likely to choose DNR orders [26][27][28], and less likely to complete any advance directives [29]. Our finding that the proportion of participants receiving CPR while ventilated significantly increased from 5.3% in 1994 to 11.3 % in 2005, p value <0.001, is interesting and perhaps reflects the increasing severity of illness and the higher proportion of critically ill patients seen in hospitals throughout the US during the study period.…”
Section: Discussionmentioning
confidence: 99%